Pengaruh Permainan Tradisional Boy-Boyan dalam Meningkatkan Koordinasi Mata-Tangan Siswa Kelas V SD Negeri Pakuwangi - M Mimbar; Ayi Suherman; Tedi Supriyadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effect of the traditional game boy-boyan on improving hand–eye coordination skills of fifth-grade students at SD Negeri Pakuwangi. The method used was a quantitative approach with an experimental method using a one group pretest–posttest design involving 22 students selected through total sampling technique. The instrument used was the hand–eye coordination test (Child Ball Test). The results showed an increase in the average score from 11.05 in the pretest to 17.45 in the posttest, with a significance value of 0.000 (p < 0.05), indicating a significant effect. In conclusion, the traditional game boy-boyan is moderately effective in improving students’ hand–eye coordination skills. Keywords: Boy-Boyan, Hand–Eye Coordination, Physical Education, Primary School Students, Traditional Games